2018
DOI: 10.1016/j.jpeds.2017.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Crying Time and RORγ/FOXP3 Expression in Lactobacillus reuteri DSM17938-Treated Infants with Colic: A Randomized Trial

Abstract: ClinicalTrials.gov: NCT00893711.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 40 publications
4
110
0
2
Order By: Relevance
“…Gut microbiome differences at baseline and following intervention varied across studies, depending on the physical health condition and type of analysis conducted. Compared to healthy controls, studies showed that infants with colic have an atypical microbial profile (Mentula et al, ; Pärtty et al, ; Savino et al, ), including lower levels of Bifidobacterium (Pärtty et al, ), consistent with the extant literature (Rhoads et al, ; de Weerth, Fuentes, Puylaert, & de Vos, ). Intervention had no effect on measures of the whole microbiome in infants with colic or IBS (Baldassarre et al, ; Fatheree et al, ; Nation et al, ; Roos et al, ; Shulman et al, ; Sung et al, ), although this may be at least partly attributable to the shallow depth of resolution in analyses.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Gut microbiome differences at baseline and following intervention varied across studies, depending on the physical health condition and type of analysis conducted. Compared to healthy controls, studies showed that infants with colic have an atypical microbial profile (Mentula et al, ; Pärtty et al, ; Savino et al, ), including lower levels of Bifidobacterium (Pärtty et al, ), consistent with the extant literature (Rhoads et al, ; de Weerth, Fuentes, Puylaert, & de Vos, ). Intervention had no effect on measures of the whole microbiome in infants with colic or IBS (Baldassarre et al, ; Fatheree et al, ; Nation et al, ; Roos et al, ; Shulman et al, ; Sung et al, ), although this may be at least partly attributable to the shallow depth of resolution in analyses.…”
Section: Discussionsupporting
confidence: 60%
“…Second, prebiotic psyllium fiber reduced pain frequency, but not severity, compared to placebo in children with IBS (Shulman et al, ). Third, Savino et al () reported elevated levels of fecal calprotectin in infants with colic compared to healthy controls at baseline, which declined over the intervention period only in the probiotic treatment group—although this was the only study (of five) to report an effect on fecal calprotectin. No negative treatment‐associated effects were reported across the studies.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Using a microarray technique and prospectively following a defined newborn population in Nijmegen, Holland, de Weerth et al found that the “top 10% of crybabies” harbored increased Proteobacteria, a group that would encompass both Klebsiella and E. coli . Two studies showed reduced lactobacilli, and 2 studies (1 our own) have shown elevated fecal calprotectin, a marker of gut inflammation …”
Section: Evidence From Human Trials: Absent Evolving or Conclusive?mentioning
confidence: 92%